1997
DOI: 10.1021/ja962023c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Properties of 4,8,12-Trioxa-12c-phospha-4,8,12,12c-tetrahydrodibenzo[cd,mn]pyrene, a Molecular Pyroelectric

Abstract: The title compound (4) was synthesized, and its crystalline structure was determined. The molecule has C 3 v point symmetry and crystallizes in the trigonal space group R3m. Crystal data for 4:  a = 16.6710(13) Å, b = 16.6710(13) Å, c = 4.2590(3) Å, α = β = 90°, γ = 120°, Z = 3, R(F) = 0.0234. The material has a permanent polarization and consequent pyroelectric properties. The room temperature pyroelectric coefficient was found to be −3 ± 2 μC m-2 K-1, which is in accordance with a calculated value of −3.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
88
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 51 publications
3
88
0
3
Order By: Relevance
“…In order to resolve the discrepancy we have re-determined the absolute morphology of three phosphangulene crystals: the original crystal and two new crystals of similar morphology. This was done using data collected on a Siemens SMART area detector diffractometer with Mo Ka radiation at 120 K. All three crystals were found to have the same absolute configuration as originally determined, but it was found that the morphology presented previously [4] was in fact in error. The morphology determined for the three instances was the same, namely with the polar c axis pointing towards the pointed end of the crystals, which is opposite to the direction previously reported.…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…In order to resolve the discrepancy we have re-determined the absolute morphology of three phosphangulene crystals: the original crystal and two new crystals of similar morphology. This was done using data collected on a Siemens SMART area detector diffractometer with Mo Ka radiation at 120 K. All three crystals were found to have the same absolute configuration as originally determined, but it was found that the morphology presented previously [4] was in fact in error. The morphology determined for the three instances was the same, namely with the polar c axis pointing towards the pointed end of the crystals, which is opposite to the direction previously reported.…”
mentioning
confidence: 92%
“…[4] Phosphangulene, Figure 1, crystallizes in the changes linearly with temperature (V(T) aTb) and the molecular dipole moment is considered independent of temperature, the pyroelectric coefficient is given as [4] where Z is the number of molecules in the unit cell.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations